EAFU program (2019)
The Elite Athlete Friendly University (EAFU) program supports Australia`s elite athletes to achieve academic excellence while also pursuing a sporting career. The value of combining both sport and higher education to achieve greater life success is well recognised across the university and sporting sectors. There are 41 universities across Australia that are part of the EAFU network. Each of these universities provides academic support and flexibility to endorsed elite student-athletes.